1999
DOI: 10.1107/s0907444998014747
|View full text |Cite
|
Sign up to set email alerts
|

Refined structure of the FKBP12–rapamycin–FRB ternary complex at 2.2 Å resolution

Abstract: The structure of the FKBP12-rapamycin-FRB ternary complex has now been refined at 2.2 A resolution. The cell-cycle arrest agent rapamycin binds FK506-binding protein (FKBP12) and the FKBP12-rapamycin binding (FRB) domain of FKBP12-rapamycin associated protein (FRAP) simultaneously, and the inhibition of FRAP is responsible for rapamycin's biological activity. The conformation of rapamycin in the ternary complex is very similar to that observed in the FKBP12-rapamycin binary complex, with an r.m.s. difference o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 29 publications
3
121
0
2
Order By: Relevance
“…mTORC1 is therefore regarded as an attractive target for cancer therapy, and there is currently a high level of interest in the development of pharmacological inhibitors of mTORC1. mTORC1 is inhibited allosterically by the natural product rapamycin (sirolimus), which interacts with the FKBP12-rapamycin-binding domain in mTOR in complex with FKBP12 (25,26). Rapamycin has been shown previously to abolish the binding of raptor to mTOR in phosphate-containing buffers (27,28).…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 99%
“…mTORC1 is therefore regarded as an attractive target for cancer therapy, and there is currently a high level of interest in the development of pharmacological inhibitors of mTORC1. mTORC1 is inhibited allosterically by the natural product rapamycin (sirolimus), which interacts with the FKBP12-rapamycin-binding domain in mTOR in complex with FKBP12 (25,26). Rapamycin has been shown previously to abolish the binding of raptor to mTOR in phosphate-containing buffers (27,28).…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 99%
“…The rapamycins (rapamycin and rapalogs) are allosteric inhibitors that, in complex with FKBP12, target the FRB domain adjacent to the catalytic site of mTOR (9,10). Intriguingly, both in vitro and in vivo studies showed that the FRB in mTORC2 is inaccessible to rapamycins as indicated by the lack of suppression of the mTORC2 substrate AKT (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically used rapamycins (rapamycin and rapalogs) partially inhibit mTOR through allosteric binding to the FKBP12-rapamycin binding domain adjacent to the catalytic site of mTORC1 (12,13). These compounds do not directly target mTORC2 and do not completely block all mTORC1 outputs.…”
Section: Introductionmentioning
confidence: 99%